Development of thermodynamically stable nanostructured lipid carrier system using central composite design for zero order permeation of Econazole nitrate through epidermis. (June 2013) - Keshri, Lav; Pathak, Kamla
<x xml:space="preserve">Abstract</x> The investigation was aimed at developing thermodynamically stable topical delivery system of nanostructured lipid carrier of econazole nitrate (EN) for the treatment of deep seated fungal infection by improving its permeability. Fifteen formulations (F1–F15) of nanostructured lipid carriers (NLCs) were prepared by solvent injection technique using central composite design and characterized for particle size and % entrapment efficiency. Closeness in the results, guided the selection of five NLC formulations which were formulated as hydrogels (G1–G5) using Carbopol 934. The permeation studies of gels demonstrated G3 with flux rate of 3.21 ± 0.03 µg/cm2/min (> target flux of 1.46 µg/cm2/min) as the best formulation that exhibited zero order permeation. The amount of drug/unit area demonstrated linear dependency on flux rate. Confocal laser scanning microscopy demonstrated penetration of rhodamine red till the stratum basale due to hydration of stratum corneum. Hydrogel G3 containing NLC formulation (F5) was selected as the optimized topical gel. TEM of F5 revealed spherical particles that presented low recrystallization index of 72.35%. Stability profile for 90 days revealed insignificant change (p < 0.05) in the particle size and zeta potential indicating substantial stability of the system. Thus, EN-loaded NLC indicated better permeability and thermodynamic stability as effective topical delivery system for deep seated fungal infection.